Mengenal Rahasia Karakter Orang Jepang: Selalu Menghargai Proses, Tidak Hanya Hasil (Kajian Budaya Dalam Pendekatan Filosofis) - Iriyanto Widisuseno (Diponegoro University, 2019)
This study focuses on examining how Japanese work culture patterns respect processes, not just the results of their work. The aim is to uncover the principles and evidence that underlie the pattern of Japanese work culture that always respects the process and not only the results. This study uses philosophical methods, which are essential, comprehensive and normative analysis of the facts of life to try to unravel and explore the principles of existence of life, namely the ontological, epistemological and axiological principles. The ontological principle, describes the Japanese footing in conceptualizing the meaning, nature of life and life in the midst of the world's environment. The principle of epistemology describes the way the Japanese realize the concept of meaning and meaning of life in their world. The axiological principle describes the values that make the direction or purpose of life. The existence of the three principles of existence is interspersed and systemic. The research results formulated that ontologically, the Japanese in conceptualizing the meaning and meaning of their lives rely on Bushido's moral values (integrity, courage, generosity, respect for others, honesty and sincerity). Epistemologically, Japanese lifestyles describe ways of finding Ikigai in him. Axiologically, the goal of Japanese life is